Aspek-Aspek Ketuhanan dalam Teologi Islam: Analisis Tiga Mazhab: Mu’tazilah, Asyariyah, Al-Maturidiyah - Syawal Kurnia Putra; Muhammad Amri; Mahmuddin (Jurnal Ilmu Sosial dan Humaniora, 2023)
This article discusses the debate over divinity aspects in Islamic theology, using the literature study method. The purpose of this paper is to find out the meaning of monotheism in Islamic theology and debates related to divine aspects in Islamic theology. The results of this writing show that religion is a belief that has long existed throughout human civilization. As for the debate on the divine aspect in Islamic theology related to the nature of God, the Mu`tazilah argue that Allah is All-Knowing with His essence, not with knowledge, power and life, because all of these are attributes while attributes are something outside of matter. While the Asy`ariyah, argue that God has properties. God's justice, according to Asy'ariyah, God does as He wills, so God does not put all people into heaven unjust and if God puts all people into hell God is not unjust. Meanwhile, the understanding of justice for the Mu`tazilah implies obligations that must be respected by God. Regarding the power and will of God's Mutlat, Mu'tazilah argues that God's absolute power has been limited by the freedom that has been given to humans in determining wills and actions. whereas Asy`ari said that God is absolute in His will and power